What Style of Learning is Most Beneficial to Students? - Jenner, Lexi (My University, 2025)
In the summer of 2023, I was a student coordinator with the College of Health and Human Sciences’ Health Professions Exploration Program at Kansas State University. This program hosted sessions over many health careers to introduce students to professions they may not know about or may be considering before college. I saw through each session, students retained more and were more driven to learn more about health professions that were presented in active and engaging ways. I was intrigued to research more about what learning style is most beneficial to students in general and in health programs. I took the Health Professions Exploration Program as a start to research active learning and how this style impacts students. I found that an active learning style is most beneficial for engaging students, retaining information, and increasing performance of students in future careers. During the summer camp, data was collected on what the students thought about each session. The data that was collected shows that the students enjoyed and wanted to learn more from the sessions that were presented in an active learning style. The students were more interested in areas of health that were presented in engaging formats. The following research paper uses the data from this health camp to show that students learn and benefit from active, engaged learning. I have also researched from other sources to support my claims and observations as well as included research pertaining to health programs.